Rebelliousness and street-level bureaucrats’ discretion: evidence from Malaysia / Mohammed Salah Hassan … [et al.] - Hassan, Mohammed Salah; Raja Ariffin, Raja Noriza; Mansor, Norma; Al Halbusi, Hussam (Universiti Teknologi MARA, 2021)
Street-level bureaucrats are a fundamental part of the implementation process of any policy. This study provides an examination of the factors that shape the behavior of street-level bureaucrats at the frontlines of policy implementation. This study investigates how rebelliousness generates an impact on the discretion of street-level bureaucrats and to what extent client meaningfulness plays a moderating factor. It utilizes a survey questionnaire distributed among inspectors of the Department of Labor in the Ministry of Human Resources of Malaysia (n=241). The result of this study demonstrates that rebelliousness has a negative relationship with discretion, and client meaningfulness has a direct positive correlation with discretion. However, the relationship between rebelliousness and discretion is stronger with a high level of client meaningfulness. The objective of this study is to examine street-level bureaucrat behavior through the lens of Lipsky's theory which will provide an answer to the broad question of the factors that contribute to the existence of an imperfect implementation process. This study sheds light on the importance of client meaningfulness in moderating the behavior of street-level bureaucrats while interacting with inspectees. The novelty of this study is by highlighting two main constructs that are likely contributing to the implementation process by directly and indirectly impacting bureaucrats’ discretion: rebelliousness, and client meaningfulness.